Financial Literacy, Entrepreneurs Motivation, and Industrial Environment to Increase of SMEs Performance with a Competitive Strategy as Mediator: Theoritical Review - Kenyo Puspito Rini; Iramani Iramani (Institut Teknologi Sepuluh Nopember, 2020)
SMEs or small and medium enterprises currently have a very important position not only in employment, and the welfare of the community in the region, in many cases SMEs can stabilize the problem of social inequality. Therefore, SMEs are required to have good performance. There is a basic theory about financial literacy theory that argues that the behavior of people with a high level of financial literacy might depend on the prevalence of the two thinking styles according to dual-process theories: intuition and cognition. This study aims to examine the influence of financial literacy, entrepreneur’s motivation, industrial environment, and competitive strategy on the performance of small and medium enterprises. By classifying the result of previous research, this research found some propositions: (1) financial literacy has a significant effect on the performance of SMEs (2) entrepreneur’s motivation significantly influences the performance of SMEs (3) industrial environment significantly influences the competitive strategy (4) competitive strategies significantly influence SME performance (5) industrial environment significantly influences the performance of SMEs. This study using Partial Least Square (PLS) technique to analyze the data. The proposition as the result studies can be investigated empirically